Evolutionary Naturalism : Selected Essays. - Ruse, Michael (Taylor & Francis Ltd., 1995)
A collection of essays on the history and philosophy of evolutionary biology which put the theory of knowledge and of moral behaviour on a philosophical basis informed by contemporary evolutionary biological theory.